Intermediate expression of CCRL1 reveals novel subpopulations of medullary thymic epithelial cells that emerge in the postnatal thymus. Issue 10 (5th September 2014) - Ribeiro, Ana R.; Meireles, Catarina; Rodrigues, Pedro M.; Alves, Nuno L.
<x xml:space="preserve">Abstract</x> Cortical and medullary thymic epithelial cells (cTECs and mTECs, respectively) provide inductive microenvironments for T‐cell development and selection. The differentiation pathway of cTEC/mTEC lineages downstream of common bipotent progenitors at discrete stages of development remains unresolved. Using IL‐7/CCRL1 dual reporter mice that identify specialized TEC subsets, we show that the stepwise acquisition of chemokine (C–C motif) receptor‐like 1 (CCRL1) is a late determinant of cTEC differentiation. Although cTECs expressing high CCRL1 levels (CCRL1hi) develop normally in immunocompetent and Rag2−/−thymi, their differentiation is partially blocked in Rag2−/−Il2rg−/− counterparts. These results unravel a novel checkpoint in cTEC maturation that is regulated by the cross‐talk between TECs and immature thymocytes. Additionally, we identify new Ulex europaeus agglutinin 1 (UEA)+ mTEC subtypes expressing intermediate CCRL1 levels (CCRL1int) that conspicuously emerge in the postnatal thymus and differentially express Tnfrsf11a, Ccl21, and Aire. While rare in fetal and in Rag2−/− thymi, CCRL1int mTECs are restored in Rag2−/−Marilyn TCR‐Tg mice, indicating that the appearance of postnatal‐restricted mTECs is closely linked with T‐cell selection. Our findings suggest that alternative temporally restricted routes of new mTEC differentiation contribute to the establishment of the medullary niche in the postnatal thymus.